Changes in the firmness and other quality parameters of fresh-cut ‘Maradol’ papaya treated with additives and 1-methylcyclopropene - Chacón-López, Martina Alejandra; Carrilo-Rodriguez, Flor Asalia; Aguilera-Aguirre, Selene; García-Magaña, María de Lourdes; González, Efigenia Montalvo; Yahia, Elhadi M.; Meza-Espinoza, Libier (Emirates Journal of Food and Agriculture, 2023)
This study aimed to evaluate the effect of 1-methylcyclopropene (1-MCP) applied as pre-cutting, post-cutting, and double application (before and after cutting) on the changes in the firmness and quality parameters of fresh-cut ripe ‘Maradol’ papaya. Four treatments (T1 T4) were used. T1 (Control treatment): Fresh-cut ‘Maradol’ papaya slices (Control treatment or T1) dipped in 1% CaCl2 for 2 min, then sprayed with 0.1% iso-ascorbic acid and 0.05% sorbic acid. One part of the T1 slices were treated with 1000 nL/L of 1-MCP for 12 h at 10 °C (T2). T3: Fresh-cut papaya slices treated with the same additives from the whole papaya treated 1000 nL/L of 1-MCP for 12 h at 20°C. T4: Fresh-cut papaya with additives treated with 1-MCP before and after cutting. All slices were packed in polypropylene trays with a perforated cover and stored at 4 ºC. T3 and T4 slices exhibited lower firmness loss and decreased activity of pectin methylesterase, polygalacturonase, and beta-galactosidase compared to T1 and T2 slices. Moreover, T3 and T4 slices had low translucency and microbial load, complying with the European Union limit (3 log CFU/g). No significant variations in acidity, pH, and total soluble solids were noted between treatments, but higher color values were obtained in T3 and T4 slices. To the best of our knowledge, this is the first study where the combining effects of additives and 1-MCP application before and after cutting extended the shelf-life of fresh-cut ‘Maradol’ papaya for up to 13 days at 4 °C, twice the duration reported by others. Keywords: Carica papaya, Postharvest, Translucency, Quality, Shelf-life